miRNAs and Novel Food Compounds Related to the Browning Process - Lorente Cebrián, Silvia; Herrera, Katya; Milagro Yoldi, Fermín Ignacio; Sánchez, Juana; De la Garza, Ana Laura; Castro, Heriberto (2019)
Obesity prevalence is rapidly increasing worldwide. With the discovery of brown adipose tissue (BAT) in adult humans, BAT activation has emerged as a potential strategy for increasing energy expenditure. Recently, the presence of a third type of fat, referred to as beige or brite (brown in white), has been recognized to be present in certain kinds of white adipose tissue (WAT) depots. It has been suggested that WAT can undergo the process of browning in response to stimuli that induce and enhance the expression of thermogenesis: a metabolic feature typically associated with BAT. MicroRNAs (miRNAs) are small transcriptional regulators that control gene expression in a variety of tissues, including WAT and BAT. Likewise, it was shown that several food compounds could influence miRNAs associated with browning, thus, potentially contributing to the management of excessive adipose tissue accumulation (obesity) through specific nutritional and dietetic approaches. Therefore, this has created significant excitement towards the development of a promising dietary strategy to promote browning/beiging in WAT to potentially contribute to combat the growing epidemic of obesity. For this reason, we summarize the current knowledge about miRNAs and food compounds that could be applied in promoting adipose browning, as well as the cellular mechanisms involved.